Perancangan port charging terintegrasi untuk motor konversi: Studi kasus Yamaha Xeon 2010 - Muhammad Hanif; Yanuar Herlambang (Institut Seni Indonesia Yogyakarta, 2026)
The Indonesian electric vehicle market is rapidly expanding alongside technological advancements and increased environmental awareness. However, in practice, many converted electric motorcycles still employ battery charging systems that are not ergonomically designed, making them impractical and sometimes hazardous for users. Ergonomic principles emphasize the importance of designs that are effective, efficient, safe, and comfortable. For example, some designs place the battery charging port beneath the motorcycle seat to protect it from rain, but this location often proves ineffective during charging. This study aims to redesign the charging system on converted electric motorcycles to make it more practical, safe, and user-friendly. The research methods include field studies to identify user needs, ergonomic analyses to evaluate existing designs, development and iteration of a new charging port design, prototyping, and iterative user testing. The primary contribution of this work is the development of an integrated charging port design based on user experience. A user-centered design approach has been acknowledged for producing the best solutions, and the user’s experience during the charging process plays a crucial role in electric vehicle adoption. Therefore, a charging port integrated into the motorcycle body and tailored to user needs is expected to advance the design of converted electric vehicles.